A Study for Estimating the Overall Heat Transfer Coefficient in a Pilot-Scale Indirect Rotary Dryer - Henriquez-Vargas, L; Donoso-Garcia, P; Fuentes-Pereira, I; Gonzalez-Duran, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
An experimental study and dimensional analysis of the effective heat transfer coefficient in a continuous-indirect rotatube dryer using forest biomass as the granular material isare developed in the present work. The study employed a factorial design (Formula presented.) to investigate the effects of feed flow frequency (20–35–50 (Hz)), drum rotational velocity (6–8–10 (rpm)), and saturated vapor pressure (4–5–6 (bar)) on the heat transfer coefficient. During steady state conditions, the moisture content profiles and inlet and outlet temperatures were measured within the experimental region, and parameters, such as the effective heat transfer coefficient, solid retention change, and moisture content ratio were studied. The results showed that heat transfer was optimized with high solid feeding rates, low pressure, and low rotation, with solid feeding being the predominant factor. The moisture content profiles revealed a change in the hydrodynamic behavior, with the center point of the experimental region being the least optimal. The dimensional analysis yielded a Nu number as a function of Pe, Fr, and the feeding dimensionless number. A new dimensionless energy efficiency number improved the coefficient correlation from 85.88 (%) to 94.46 (%), indicating the developed model potential to predict dimensionless variables and scale continuous-indirect rotatube dryers. © 2024 by the authors.